2014
DOI: 10.1159/000356647
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits mTOR-Dependent Autophagy during Liver Ischemia/Reperfusion

Abstract: Background: Autophagy is a self-digestion system responsible for maintaining cellular homeostasis and interacts with reactive oxygen species produced during ischemia/reperfusion (I/R). Melatonin (MLT) is a potent and endogenous anti-oxidant that has beneficial effects in liver I/R injury. In this study, we examined the cytoprotective mechanisms of MLT in liver I/R, focusing on autophagic flux and associated signaling pathways. Methods: Male C57BL/6 mice were subjected to 70% liver ischemia for 60 min followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 42 publications
(43 reference statements)
7
57
0
Order By: Relevance
“…As low levels of autophagy during ischemia and early reperfusion protect against cell death, it was suggested that spontaneous upregulation of autophagy may prevent excessive apoptosis of cardiomyocytes in response to H/R. Numerous studies have also demonstrated that autophagy is a beneficial response to ischemia/reperfusion (I/R) (21)(22)(23)(24). For example, increased autophagy was demonstrated to correlate with the functional recovery of the myocardium following I/R, and cardiac myocytes exhibiting enhanced levels of autophagy were found to be negative for apoptosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…As low levels of autophagy during ischemia and early reperfusion protect against cell death, it was suggested that spontaneous upregulation of autophagy may prevent excessive apoptosis of cardiomyocytes in response to H/R. Numerous studies have also demonstrated that autophagy is a beneficial response to ischemia/reperfusion (I/R) (21)(22)(23)(24). For example, increased autophagy was demonstrated to correlate with the functional recovery of the myocardium following I/R, and cardiac myocytes exhibiting enhanced levels of autophagy were found to be negative for apoptosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…MLT is considered as a type of compound with a clinical application because of its biological functions such as improving sleep, anti-aging, regulating immunity, anti-tumor, and others [17][18][19]. Moreover, MLT inhibits mTOR-dependent autophagy in liver ischemia/reperfusion and protects the esophageal epithelial barrier through ERK1/2 signal transduction [20,21]. In addition, MLT also has anti-oxidant and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently Kang et al [158] demonstrated, using a model of liver ischemia/reperfusion (I/R) injury, that autophagic flux was increased in response to I/ R injury, but this was attenuated by melatonin via inhibiting mammalian target of rapamycin (mTOR)-dependent autophagy [158]. However, it is unclear to what extent melatonin activates mTOR-dependent or mTOR-independent pathways.…”
Section: The Role Of Melatonin On Doxorubicininduced Cardiomyocyte Cementioning
confidence: 99%
“…However, it is unclear to what extent melatonin activates mTOR-dependent or mTOR-independent pathways. The suppression of autophagy by melatonin suggested its protective role during I/R injury [158]. It seems possible that melatonin could also potentially suppress the increase in autophagic flux observed during DXR-induced cardiotoxicity; however, this aspect would have to be investigated.…”
Section: The Role Of Melatonin On Doxorubicininduced Cardiomyocyte Cementioning
confidence: 99%